Website assurance monitoring application with MD5 Hashing and SHA-26 Algorithm / Abdullah Sani Abd Rahman and Samsiah Ahmad - Abd Rahman, Abdullah Sani; Ahmad, Samsiah (Universiti Teknologi MARA, Perak, 2022)
Websites attack by falsifying the websites contents is a serious matter of websites assurance nowadays. This problem can become more crucial if the websites authority do not take regular checking or lack of specialized experts in monitoring the changes. Time consuming and growing of websites complexity is additional reasons of the inadequate website assurance. This paper presents a new framework for websites integrity assurance through a website monitoring application. The monitoring application able to detect any modification on a website to be reverted to the actual version. The Website Assurance Monitoring application has been developed based on MD5 hashing technique and SHA26 algorithm. By using Microsoft Visual Basic 6.0, the Graphical User Interfaces (GUIs) of the application to provide an easy or user-friendly monitoring application. During the implementation testing, the functionality and usability of the website assurance application have been verified by different level of computing expert users. All the expert users agreed that the website assurance application is accurate and sufficient to detect changes occurred in websites. Regarding to processing time, majority of the inexpert computing users experienced easy and fast processing. Additionally, most of these users believed that this application can increase the integrity of a website. The proposed websites assurance monitoring application is beneficial to serve the inexpert websites authority with a user-friendly application. The application can help the administrator to preserve the integrity of a website by automatically detecting any unauthorized contents changes.